Identification of factors affecting the life expectancy (LE) of Buildings in Malaysia - Mohd Subri, Syaza Aisyah; Abu Bakar, Anisah Sufiah; Razali, Nur Ain; Mohammad, Hairuddin (2024)
In Malaysia, building deterioration is always a national concern. Among the major causes is lack of maintenance which is further exacerbated by several factors that affect the building components throughout their life expectancy (LE). Nevertheless, given that the factors were considered dynamic in nature due to the changes in the people, process, environment, and technology surrounding the built environment’s realm, a generic difference in terms of its concentration of impacts is expected. Therefore, a study on revisiting the factors of life expectancy (FLE) of buildings is conducted to identify and validate the factors that might be influential. To achieve this goal, this study used a mixed methodology; literature review through multi-layered thematic (MLT) document analysis and questionnaire survey to validate all factors that influence the LE. The findings show that there are differences in terms of FLE concentration (in rankings) towards different types of building materials (wood/timber, steel, and concrete). It is expected that the result will further help other researchers in pursuing LE numbers for building components, especially in the Malaysian context and others that share similar circumstances